LEARNING LANGUAGES BY USING IDIOMS IN MOTHER TONGUE - Ш.Е., Ауелбековa (Journal of Oriental Studies, 2019)
In this article, we present Kazakh equivalents of Turkish idioms and propose to use them compara- tively. This method facilitates the memorization of new material and accelerates learning of vocabulary because learning by understanding is more effective than plain memorization. Learning figurative idioms in a language enables us to master it and trains us to understand complex texts, and clearly communicate thoughts and ideas. In the article, we compared similar Turkish and Kazakh idioms containing the word “hand” and found their equivalents. We illustrated the effectiveness of the method of using idioms and shared the observations.The work can also be a reference for translation as it contains similar linguistic materials of Kazakh, Turkish and English languages. Key words: Kazakh language, Turkish language, English language, idioms, hand.